ANALYSIS OF ENTREPRENEURIAL ORIENTATION ON BUSINESS PERFORMANCE WITH ABSORPTIVE CAPACITY AS AN INTERVENING VARIABLE - Kambali, Laraswati; Danial, R Deni Muhammad; Ramdan, Asep Muhamad (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the influence of entrepreneurial orientation on business performance of fashion MSMEs in Sukabumi with absorptive capacity as an intervening variable. Entrepreneurial orientation, which includes innovation, proactiveness and risk-taking, is believed to play a significant role in improving business performance through the ability of MSMEs to absorb, assimilate and exploit external knowledge. The study used quantitative methods with Partial Least Square (PLS) data analysis techniques. Data were collected through questionnaires involving 100 fashion MSMEs in Sukabumi. The results showed that entrepreneurial orientation has a significant positive influence on absorptive capacity (t-statistic = 28.215, p < 0.05) and business performance (t-statistic = 3.610, p < 0.05). Absorptive capacity also significantly affects business performance (t-statistic = 4.618, p < 0.05) and mediates the relationship between entrepreneurial orientation and business performance (t-statistic = 4.630, p < 0.05). The most dominant absorptive capacity dimension is exploitation, which reflects the ability of MSMEs to generate new knowledge-based innovations. The conclusion of this study is that entrepreneurial orientation supported by absorptive capacity can improve the business performance of fashion MSMEs. This research provides practical implications for MSME actors to strengthen entrepreneurial orientation and develop absorptive capacity through training and access to external knowledge.